2016
DOI: 10.1007/s00261-015-0602-x
|View full text |Cite
|
Sign up to set email alerts
|

Technical advancements and protocol optimization of diffusion-weighted imaging (DWI) in liver

Abstract: An area of rapid advancement in abdominal MRI is diffusion-weighted imaging (DWI). By

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…The single-shot EPI had the drawbacks of low spatial resolution and signal-to-noise ratio Ni et al. ( 42 ). The multi-shot EPI technique addresses this drawback.…”
Section: Discussionmentioning
confidence: 99%
“…The single-shot EPI had the drawbacks of low spatial resolution and signal-to-noise ratio Ni et al. ( 42 ). The multi-shot EPI technique addresses this drawback.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) measures the ADC values using a single exponential model, which could quantitatively reflect the diffusion motion of water molecules in tissues ( 8 ). DWI detects the physiological characteristics of tissue non-invasively by measuring the diffusion properties of water molecules ( 9 ). Several studies have applied the mean ADC value, which was significantly higher in the loose fibrosis group PDAC than in the dense fibrosis group and negatively correlated with PDAC fibrosis ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…DWI was demonstrated to be a useful adjunct sequence to DCE imaging, improving diagnostic accuracy of liver nodules compared to DCE imaging alone. Apparent diffusion coefficient (ADC) is obtained by the monoexponential model of conventional DWI with the assumption that water diffusion obeys the Gaussian law [11]. Previous studies have reported DWI has improved the sensitivity and detection rate of HCC when combined with enhanced MRI [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported DWI has improved the sensitivity and detection rate of HCC when combined with enhanced MRI [12]. However, some reports have also suggested that it may be difficult to differentiate HCC from other solid hepatic lesions like FNH, HCA, and metastasis by DWI due to the overlapping ADC values between HCC and these solid lesions as a result of their increased cellularity [11, 13, 14]. In 2005, Diffusion kurtosis MR imaging (DKI), first proposed by Jensen et al [15], was described as water diffusion deviates from the Gaussian law due to the complexity of microenvironment, such as cell membranes, vessels, or macromolecules.…”
Section: Introductionmentioning
confidence: 99%